A new and an unrecorded species of the family Psychidae (Lepidoptera) from Korea, with an annotated catalogue. Issue 11 (26th March 2016) - Roh, Seung Jin; Banasiak, Grzegorz; Byun, Bong-Kyu
Abstract: In this study, a total of nine species of the family Psychidae were recognised from Korea. Among them, Psyche yeongwolensis sp. nov. is described as new to science. Also, a species, Proutia maculatella Saigusa et Sugimoto, is reported for the first time from Korea. All available material were dissected and illustrated. Also, an annotated catalogue of the family Psychidae from Korea is provided.